Team learning and context; assessing the relationship between team-learning activities and contextual factors of team-learning environment and team-configurations - Denekens J; Van Petegem P; Van Linge R; Timmermans O (Dove Medical Press, 2011)
Olaf Timmermans1, Roland Van Linge2, Peter Van Petegem3, Joke Denekens4 1Faculty of Medicine, Nursing and Midwifery Science, University of Antwerp, Belgium; 2University Medical Centre Utrecht, Department of Nursing Sciences, Utrecht University, The Netherlands; 3Institute of Education and Information Sciences, University of Antwerp, Belgium; 4Department General Practice, University of Antwerp, Belgium Background: The prevalence of team-learning activities in nursing teams is influenced by contextual factors. Although team learning is important for nursing teams to perform, there is a paucity of research exploring the relationship between team-learning activities and contextual factors in nursing teams. The aim of this study was to study the relationship between team learning and contextual factors of the nursing team. Methodology: Correlation and multiple regression analyses were used to study the relationship between team learning and five contextual variables. One contextual variable represented the overall environment for learning, and the other four contextual variables characterized basic configurations of organizational characteristics of nursing teams. An interrelation between the contextual variables was expected, so multiple regression models were tested for multicollinearity by regression commonality analysis to detect unique and common contributions of each independent variable. Findings: Results of this study indicate that team-learning activities in nursing teams can be enhanced by contextual factors such as: (1) strengthening stimulation of the psychological safety, (2) openness, (3) shared goals, and (4) an open, external-oriented view. Multiple regressions yielded three models that explain 76%, 81%, and 83% of the variance in team learning. Commonality analyses showed the importance of interrelationships between the contextual factors. Practical implications: Nurses undertake team-learning activities to process information needed to perform production-oriented and innovation-oriented tasks. Contextual variables affect the prevalence of team-learning activities in nursing teams. To enhance team learning in nursing teams, management and nurses should strengthen the facilitation of a development oriented team configuration and an intense team-learning environment. Keywords: team learning, nursing, contextual factors